ELEVATIONAL DISTRIBUTION OF TREE DIVERSITY IN LOWER HIMALAYA: A CASE STUDY OF PHULCHOKI HILL, NEPAL - Kattel, Ruska; Devkota, Bimala; K.C., Laxman (International Journal of Environment, 2015)
Changes in tree species composition with elevation have been studied at three distinct altitudinal ranges on the basis of dominance, in sub-tropical and temperate forests on south slopes of Phulchoki hill, central part of lower Himalaya, Nepal. The greatest number of tree species was found in the low altitude (1600 m), followed by intermediate altitude (1950 m). The highest altitude (2650 m) contained only one distinct tree species (Oak). Site I has higher species diversity (Shannon Index: 2.1863, Evenness Index: 0.852) and density (5575 individual per hectare) dominated by Castonopsis indica, Quercus glauca, Myrica esculenta and myrsine capitellate. Site II has average species diversity (Shannon Index: 1.759, Evenness Index: 0.9) and an average density (2150 individual per hectare) dominated by Rhododendron arboretum, Castanopsis tribuloides and Quercus incana. At site III the forest is entirely dominated by Quercus semicarpifolia, a high altitude Oak. A linear trend of decreasing tree species diversity and density along with elevations was seen which might be because of intense afforestation by communities at lower elevation as site I and II under community managed forest and lower altitudinal ecozone with clear zonation of elevational vegetation types. International Journal of Environment Volume-4, Issue-3, June-August 2015 Page: 130-139